2021
DOI: 10.1111/apm.13179
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of pharyngeal bacterial pathogens among healthy adolescents and young adults

Abstract: The pharyngeal mucosa can be colonized with bacteria that have potential to cause pharyngotonsillitis. By the use of culturing techniques and PCR, we aimed to assess the prevalence of bacterial pharyngeal pathogens among healthy adolescents and young adults. We performed a cross-sectional study in a community-based cohort of 217 healthy individuals between 16 and 25 years of age. Samples were analyzed for Group A streptococci (GAS), Group C/G streptococci (SDSE), Fusobacterium necrophorum, and Arcanobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Though their ages and gender-ratio matched the patients well, controls were less often smokers and may not represent a normative population. However, the swabs were obtained and processed in the same way as for patients and our findings ( S. pyogenes 4%, F. necrophorum 9%, and S. dysgalactiae 5% ) are similar to previously reported culture-based detection rates for the suggested pathogens ( S. pyogenes 1.1–2.3%, F. necrophorum 3.8–9.4%, and S. dysgalactiae 3.1–5.5%) [ 6 , 17 –[ 18 , 30 ]– 31 ]. Studies using polymerase chain reaction (PCR) methodology have reported higher detection rates with low quantities of bacteria present in the samples [ 30 , 32 ], which is in agreement with our finding of significantly less abundance (semi-quantitative count) of S. pyogenes and F. necrophorum in controls compared to patients.…”
Section: Discussionsupporting
confidence: 91%
“…Though their ages and gender-ratio matched the patients well, controls were less often smokers and may not represent a normative population. However, the swabs were obtained and processed in the same way as for patients and our findings ( S. pyogenes 4%, F. necrophorum 9%, and S. dysgalactiae 5% ) are similar to previously reported culture-based detection rates for the suggested pathogens ( S. pyogenes 1.1–2.3%, F. necrophorum 3.8–9.4%, and S. dysgalactiae 3.1–5.5%) [ 6 , 17 –[ 18 , 30 ]– 31 ]. Studies using polymerase chain reaction (PCR) methodology have reported higher detection rates with low quantities of bacteria present in the samples [ 30 , 32 ], which is in agreement with our finding of significantly less abundance (semi-quantitative count) of S. pyogenes and F. necrophorum in controls compared to patients.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, these criteria remain useful. Importantly, due to the known asymptomatic tonsillar carriage of F. necrophorum and GAS [ 12 , 18 ], the aim of clinical criteria in pharyngotonsillitis should not be to identify all cases positive for F. necrophorum or GAS, but preferably target cases most likely to benefit from treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, as of yet, antibiotic efficacy in F. necrophorum pharyngotonsillitis has not been evaluated. In addition, tonsillar carriage rates of F. necrophorum have varied between 0-21% [2,[12][13][14][15][16][17][18] in studies including adolescents and young adults, complicating the interpretation of a positive finding. Nevertheless, the tonsillar carriage rate of GAS (by PCR) in similar age groups have been found to be 9% [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization was most commonly seen in patients with GAS infection, while those with F. necrophorum had the highest rates of recurrence of pharyngotonsillitis (15–30 days) ( Table 2 ) and peritonsillar abscess ( Figure 3 ). It can be difficult to interpret a finding of F. necrophorum in pharyngotonsillitis because most cases occur in the same age group where tonsillar carriage is seen [ 11 , 22 ]. We found a test positivity rate of F. necrophorum of 28%, and higher (38%) among patients aged 13–30 years, in line with previous studies [ 8–10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%